Breakfast habit of high school going students in Bangladesh: a correspondence analysis - Khan, Md Abrar Ashfaq; Sonia, Jakia Benta; Ohid Ullah, Mohammad (Asian Journal of Medical and Biological Research, 2024)
The importance of breakfast in maintaining a healthy lifestyle is well-documented, yet breakfast omission remains prevalent among children and teenagers, leading to negative health and academic outcomes. The purpose of this study is to identify the association between various levels of breakfast consumption and other related factors. A secondary cross-sectional dataset was used in this study to detect the habits of breakfast consumption and its association between other related factors. As chi-square test shows the association between the two attributes, corresponding analysis was applied in this study to see the level-wise association between the attributes. The dataset contains a total of 509 individuals that were enrolled in high school education in northeastern region of Bangladesh. The results of the study indicated that around fifty percent of the children are skipping breakfast and most of them are from Habiganj and Sunamganj districts. It is found that urban students are higher tendency to miss breakfast compare to rural area. It is also observed that lower levels of parental education are highly associated with not taking and/or irregular taking breakfast. In correspondence analysis, the results revealed that students whose mothers are engaged in government or private sector jobs tend to have a consistent breakfast routine, however, in a chi-square test it was found that mother’s occupation and breakfast consumption is not significantly associated. It indicates correspondence analysis is more suitable to discover the level-wise association. Taken together, it is concluded that parental education and occupation may increase the taking breakfast of school children. This study highlights the need to advocate for breakfast intake among adolescents. The study concludes that correspondence analysis is essential to know the level-wise association between the attributes. Asian J. Med. Biol. Res. 2024, 10(3), 99-109